Kalye musika local plucked string musical instrument hub - Riego, Jessica Kim E. (College of Architecture, University of the Philippines Diliman, 2019)
Architecture as a building tool in restoring the local plucked string musical instrument making industry. This project is located in Guagua, Pampanga, where there is an existing guitar making district, and where a growth corridor is identifies. It integrates institutional facilities and tourism to showcase and further enrich the plucked string making industry of San Antonio, Guagua. It aims to empower luthiers to flourish in their craft, providing training and support facilities, as well as retail spaces that could be leased. The spaces are anchored in a pedestrian street or kalye that allows visual accessibility on all facilities, as well as variety of activities that will create an attraction such as food, outdoor exhibits, and performance spaces. Ultimately, through integrating institutional and commercial spaces for attraction that introduce variety of experiences that will affect the perception of the public with locally made.